The Effect of Accounting Literacy and Intellectual Intelligence on Interest in Becoming an Auditor with Remote Audit Competency Needs as Moderator - Sihar Tambun; Anjeli Frisilia; Riris Rotua Sitorus (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study analyzes if accounting and intellectual literacy moderate remote audit ability and auditor interest. This research on accounting literacy, intellectual intelligence, and remote audit proficiency can boost auditor interest. This study includes 150 people of various ages and education. The quantitative study uses structural equation modelling. Causality studies examine direct and moderating variable effects. This study tests data quality using Smart PLS analysis, a variance-based or component-based structural equation model. The program called Smart PLS. This study demonstrated that intellectual intelligence affects auditor interest, not accounting literacy. The desire to become an auditor increases with intelligence. Interest in being an auditor rises with the requirement for remote audit competency. Accounting literacy and intelligence can be affected by remote audit competency. According to this report, individuals and companies should prioritize accounting literacy, intellectual intelligence culture, and remote audit ability. Remote audit competency is important because understanding its main role affects interest in becoming an auditor and managing accounting literature and intellectual intelligence on that desire. Study results show this. These findings can help people become auditors and organizations train auditors